Refugee entrepreneurship: A systematic literature review and future research agenda - Lång, Stefan (Elsevier, 2025)
While scholars have traditionally studied successful entrepreneurship cases, they have focused less on studying how victims of adversity engage in entrepreneurial actions to create a better future for themselves and others. It is argued that while entrepreneurs are a major force of disruption, they possess resilience that enables them to cope with persistent and substantial adversity. Refugees facing extreme adversity can engage in entrepreneurial activities to create economic gains. While scholarly attention has been directed towards immigrant and migrant entrepreneurship, refugees present a different perspective due to the severity and persistence of their adversity. In this study, we conducted a systematic review of the refugee entrepreneurship literature. A total of 83 articles published between 2000 and 2021 across 22 entrepreneurship journals were analyzed. We identified four widely used theoretical lenses, namely mixed embeddedness, social networks, institutional theory and opportunity. Studies have primarily been conducted among refugees in European host countries, with an absence of studies in neighboring countries or refugee camps. Results show that scholarly enquiry into refugee entrepreneurship is still in its nascent stages with respect to theoretical perspective, method and data. The study contributes to the extant literature by outlining several potential research streams that could strengthen the notion of refugees in the entrepreneurship literature.